VILLAGE GOVERNMENT COMMUNICATION STRATEGY WURING IN INCREASING AWARENESS IS MANDATORY PROPERTY TAXES Qualitative Descriptive Study on Wuring Village Government Alok Barat District, Sikka Regency - Mayelus Dori Bastian; Yakobus Henyorius Mayofi (Sean Institute, 2023)
Land and Building Tax (PBB) is a tax levied on land and buildings because of the advantages and better socio-economic position for people or entities that have a right to or benefit from them. Wuring Village is one of 4 sub-districts in the West Alok District which has taxpayers whose number continues to increase every year. Within a period of three years, in Wuring Village there has been an increase in the number of taxpayers as many as 32 taxpayers, but the data recap of the realization of PBB-P2 payments (Urban Rural Land Building Tax) still shows that the increase in the number of taxpayers is not in line with the receipt of PBB-P2 payments. in Wuring Village which is still under the predetermined provisions. The public's assumption of wrong taxes has an impact on the state and therefore needs to be reduced, especially considering these obstacles, the government must make efforts to make people understand the benefits of paying efficient business taxes, namely by conducting socialization of approaches to paying taxes. This study aims to identify and describe the communication strategy carried out by the Wuring Village Government to increase public awareness in paying taxes (PBB) in Wuring Village, Alok Barat District, Sikka Regency. The results of this study are the communication strategy implemented by the Wuring Sub-District Government in an effort to increase the awareness of taxpayers in their area through two ways, namely socialization and improving excellent service. This is an effort to implement a form of communication that is persuasive, informative, and educative. The communication strategy implemented by the Wuring Village Government in the form of socialization and improvement of excellent service has not been able to run optimally because there are various obstacles in the form of sociological barriers, anthropological barriers, psychological barriers, and also semantic barriers. These various obstacles are an evaluation study for the Wuring Village Government for planning and improving future strategies.